PENGARUH PERSONAL SELLING, SALES PROMOTION TERHADAP PENINGKATAN VOLUME PENJUALAN (STUDI EMPIRIS PADA CV.LION KOTA TERNATE 2013-2017 ) - Hidayanti, Ida; Abdulhaji, Sulfi (Jurnal Manajemen Sinergi, 2019)
This study aims to test whether Personal Selling, SalesPromotion has an effect on Increasing Sales Volume at Cv. Lion City ofTernate. The population in this study is all sales reports for 2013-2017on CV. Lion Honda Ternate City. The sampling method uses saturatedsamples or sampling census where all members of the population aresampled. So that the sample in this study amounted to 60. Thetechnique of collecting data used was by means of documentationobservation techniques by collecting lists of increasing sales volumes.The analytical method used is multiple regression analysis with the helpof SPSS 23.0 Software. The results of this study found that the PersonalSelling variable had an effect on Sales Volume, and the Sales Promotionvariable had no effect on Sales Volume.